Ответ(ы) на вопрос:
Гость
ОДЗ
{ x < 5
{ x < ∛35 ≈ 3,27 => x < ∛35
lg (35 - x^3) = lg (5 - x)^3
35 - x^3 = (5 - x)^3
35 - x^3 - (5 - x)^3 = 0
35 - x^3 + (x - 5)^3 = 0
35 - x^3 + (x^3 - 15x^2 + 75x - 125) = 0
- 15x^2 + 75x - 90 = 0
15x^2 - 75x + 90 = 0 /:15
x^2 - 5x + 6 = 0
D = 1
x1 = 2 ∈ ОДЗ
x2 = 3 ∈ ОДЗ
Ответ
2; 3
Гость
ОДЗ
{35-x³>0⇒x⇒x<∛35
{5-x>0⇒x<5
x∈(-∞;∛35)
lg(35-x³)=lg(5-x)³
35-x³=(5-x)³
35-x³-125+75x-15x²+x³=0
-15x²+75x-90=0
x²-5x+6=0
x1+x2=5 U x1*x2=6
x1=2 U x2=3
Не нашли ответ?
Похожие вопросы